Digital Code-Division Multiplexing Channel Aggregation for Mobile Fronthaul Architecture With Low Complexity - Haibo Li; Qi Yang; Songnian Fu; Ming Luo; Xiang Li; Zhixue He; Peng Jiang; Yongpiao Liu; Shaohua Yu (IEEE Photonics Journal)
A low-complexity mobile fronthaul architecture via digital code-division multiplexing (CDM) is proposed to enable channel aggregation of 4G-LTE signals. In comparison with traditional frequency division multiplexing based aggregation scheme, the fast Fourier transformation/inverse fast Fourier transformation operations are replaced by simple sign selection and addition, leading to the significant reduction of computational complexity. Moreover, synchronous transmission of both the I/Q waveforms of wireless signals and the control words (CWs) used for the purpose of control and management using the CDM approach is also presented to be compliant with the common public radio interface (CPRI). In a proof-of-concept experiment, we demonstrate the transmission of 48 × 20 MHz LTE signals with CPRI equivalent data rate of 59 Gb/s, achieving an average error vector magnitude (EVM) of ∼3.6% and ∼4.3% after 5 and 20 km transmission over standard single-mode fiber (SSMF), respectively. Furthermore, we successfully demonstrate the transmission of 32 × 20 MHz LTE signals together with CPRI-compliant CWs, corresponding to CPRI-equivalent data rate of 39.32 Gb/s, only using single optical wavelength channel with analog bandwidth of ∼1.96 GHz. After transmission over 5 km SSMF, CWs can be error-free recovered while the LTE signals are recovered with an EVM of ∼3.6%.